Protocol for the avatar acceptability study: a multiperspective cross-sectional study evaluating the acceptability of using patient-derived xenografts to guide personalised cancer care in Australia and New Zealand. Issue 8 (8th August 2018) - Wakefield, Claire E; Doolan, Emma L; Fardell, Joanna E; Signorelli, Christina; Quinn, Veronica F; Tucker, Kathy F; Patenaude, Andrea F; Marshall, Glenn M; Lock, Richard B; Georgiou, Gabrielle; Cohn, Richard J
Abstract : Introduction: Patient-derived xenografts (PDXs) have the potential to transform personalised cancer care, however, little is known about the acceptability of using PDXs to guide treatment decision-making. Given that patient and community preferences can influence satisfaction with care as well as the success of new technologies, we will evaluate the acceptability of PDXs in individuals affected by cancer and community comparisons. Methods and analysis: This comparative cross-sectional study will recruit 323 individuals affected by cancer (cancer survivors (of childhood or adult cancer) and parents of childhood cancer survivors) and 323 community comparisons (adults and parents). We will collect data via structured interviews and questionnaires. To determine the acceptability of PDXs, we will assess five domains: willingness to use PDXs when/if diagnosed with cancer, perceived advantages and disadvantages of PDXs, maximum acceptable out-of-pocket costs per patient, maximum acceptable turnaround time to receive results and maximum acceptable number of mice sacrificed per patient. The primary endpoint will be participants' decisional balance ratio (calculated as participants' advantages ratings divided by perceived disadvantages ratings). Ethics and dissemination: The study protocol has been approved by the South Eastern Sydney Local Health District Human Research Ethics Committee (HREC:12/173) and UNSW Sydney (HC15773). The results will be disseminated in peer-reviewed journals and at scientific conferences. A lay summary will be published on the Behavioural Sciences Unit website.